Pre-mRNA Processing Factors and Retinitis Pigmentosa: RNA Splicing and Beyond - Yang, Chunbo; Georgiou, Maria; Atkinson, Robert; Collin, Joseph; Al-Aama, Jumana; Nagaraja-Grellscheid, Sushma; Johnson, Colin; Ali, Robin; Armstrong, Lyle; Mozaffari-Jovin, Sina; Lako, Majlinda (Frontiers in Cell and Developmental Biology, 2021)
Retinitis pigmentosa (RP) is the most common inherited retinal disease characterized by progressive degeneration of photoreceptors and/or retinal pigment epithelium that eventually results in blindness. Mutations in pre-mRNA processing factors (PRPF3, 4, 6, 8, 31, SNRNP200 and RP9) have been linked to 15-20% of autosomal dominant RP (adRP) cases. Current evidence indicates that PRPF mutations cause retinal specific global spliceosome dysregulation, leading to mis-splicing of numerous genes that are involved in a variety of retina-specific functions and/or general biological processes, including phototransduction, retinol metabolism, photoreceptor disk morphogenesis, retinal cell polarity, ciliogenesis, cytoskeleton and tight junction organisation, waste disposal, inflammation, and apoptosis. Importantly, additional PRPF functions beyond RNA splicing have been documented recently, suggesting a more complex mechanism underlying PRPF-RPs driven disease pathogenesis. The current review focuses on the key RP-PRPF genes, depicting the current understanding of their roles in RNA splicing, impact of their mutations on retinal cell’s transcriptome and phenome, discussed in the context of model species including yeast, zebrafish, and mice. Importantly, information on PRPF functions beyond RNA splicing are discussed, aiming at a holistic investigation of PRPF-RP pathogenesis. Finally, work performed in human patient-specific lab models and developing gene and cell-based replacement therapies for the treatment of PRPF-RPs are thoroughly discussed to allow the reader to get a deeper understanding of the disease mechanisms, which we believe will facilitate the establishment of novel and better therapeutic strategies for PRPF-RP patients.